A Wanted Man: Jack Reacher #17 - Child, Lee (New York : Delacorte Press, 2012)
Hitching a ride to Virginia in a car with three strangers, Jack Reacher finds himself unwittingly involved in a massive conspiracy that makes him a threat.
Keywords: Reacher, Jack (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Private investigators -- Fiction; Murder -- Investigation -- Fictin; Conspiracies -- Fiction; Reacher, Jack (Fictional character) -- Fiction; Detectives -- Fiction; Homicide -- Fictin; Conspiracies -- Fiction; Suspense fiction; Mystery fiction